2008
DOI: 10.1108/10222529200800004
|View full text |Cite
|
Sign up to set email alerts
|

A proposed reporting framework for HIV/Aids disclosure by listed South African companies

Abstract: This article proposes a disclosure framework for the reporting of HIV/Aids-related information in annual reports to address the lack of consistency in current disclosure practices. A literature review was undertaken to determine business risks and responses relating to the disease, followed by an empirical investigation into voluntary disclosure on HIV/Aids by companies listed on the JSE Securities Exchange. The investigation consisted of a thematic content analysis for the period 1998 to 2004. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Nationally, the negative effects of the AIDS pandemic manifested in a number of ways; annual GDP fell as active labour force numbers fell (Barako et al, 2010), tax revenues shrunk while healthcare costs increased substantially (Du Bruyn, 2008), and average life expectancy was drastically shortened (CIA Factbook, 2011). Corporate SA was also affected by the AIDS epidemic through a variety of channels, including increased absenteeism leading to lower productivity and high incidences of labour turnover, resulting in the loss of skilled labour and thus increased costs of recruitment and training (Dickinson, 2004;Du Bruyn, 2008). These effects did not only contributed directly to the erosion of the competitiveness of SA companies, but also impacted negatively on their profitability and sustainability (Fig, 2005;Rampersad, 2010).…”
Section: Hiv/aids and South Africa: Context And Corporate Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nationally, the negative effects of the AIDS pandemic manifested in a number of ways; annual GDP fell as active labour force numbers fell (Barako et al, 2010), tax revenues shrunk while healthcare costs increased substantially (Du Bruyn, 2008), and average life expectancy was drastically shortened (CIA Factbook, 2011). Corporate SA was also affected by the AIDS epidemic through a variety of channels, including increased absenteeism leading to lower productivity and high incidences of labour turnover, resulting in the loss of skilled labour and thus increased costs of recruitment and training (Dickinson, 2004;Du Bruyn, 2008). These effects did not only contributed directly to the erosion of the competitiveness of SA companies, but also impacted negatively on their profitability and sustainability (Fig, 2005;Rampersad, 2010).…”
Section: Hiv/aids and South Africa: Context And Corporate Responsesmentioning
confidence: 99%
“…Whilst we find that many companies tend to vaguely acknowledge that HIV/AIDS will have an impact on their economic performance, they have not provided detailed assessments of this likely impact. Lawrence andSamkin (2005) andDu Bruyn (2008) asserted that this absence of disclosure could be related to the negative consequences for the market if inaccurate or confidential information was to be released. In addition, and as suggested by O'Donovan (2002) and Mahajan et al (2007), a symbolic strategy of concealment of financial information may be appropriate to avoid any criticism from certain constituents that the company is not sufficiently contributing (in financial terms) to their 'cause '.…”
Section: First Period (2003 To 2006/7): From the Symbolic To The Subsmentioning
confidence: 99%
“…Furthermore, the Global Reporting Initiative [26] emphasized on firms to understand the social and environmental impact of HIV/AIDS on their ordinary activities to adopt a strategic plan to address it. Moreover, the JSE and the Institute of Chartered Accountants encouraged a formal approach for HIV/AIDS disclosure by firms [27].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemics affect daily life and production activities. Studies have found that during an epidemic period, the labor participation rate, labor productivity, total wage income, and human capital decrease significantly [5,6], while the redundancy rate, the employee absenteeism rate, and operating costs increase significantly [7,8]. In addition, the International Labour Organization has suggested that acquired immune deficiency syndrome (AIDS) directly reduces the average working life of employees and increases the non-business expenses of enterprises, such as medical care, funerals [9], and others.…”
Section: Epidemic Shocks and Enterprise Innovationmentioning
confidence: 99%
“…Let f k denote the crowding-out effect of the cost of epidemic prevention. From Equation (8), the firm incurs an increased marginal cost of production due to the crowding-out effect. In other words, the cost of epidemic prevention increases the marginal cost c incurred by the firm in its production process.…”
Section: Epidemic Shocks and Enterprise Innovationmentioning
confidence: 99%